A Soft Pneumatic Two-Degree-of-Freedom Actuator for Endoscopy - Decroly, Gilles; Lambert, Pierre; Delchambre, Alain (Frontiers in Robotics and AI, 2021)
The rise of soft robotics opens new opportunities in endoscopy and minimally invasive surgery. Pneumatic catheters offer a promising alternative to conventional steerable catheters for safe navigation through the natural pathways without tissue injury. In this work, we present an optimized 6 mm diameter two-degrees-of-freedom pneumatic actuator, able to bend in every direction and incorporating a 1 mm working channel. A versatile vacuum centrifugal overmoulding method capable of producing small geometries with a variety of silicones is described, and meter-long actuators are extruded industrially. An improved method for fibre reinforcement is also presented. The actuator achieves bending of more than 180° and curvatures of up to 0.1 mm-1. The exerted force remains below 100 mN, and with no rigid parts in the design, it limits the risks of damage on surrounding tissues. The response time of the actuator is below 300 ms and therefore not limiting for medical applications. The working space and multi-channel actuation are also experimentally characterized. The focus is on the study of the influence of material stiffness on mechanical performances. As a rule, the softer the material, the better the energy conversion, and the stiffer the material, the larger the force developed at a given curvature. Based on the actuator, a 90 cm-long steerable catheter demonstrator carrying an optical fibre is developed and its potential for endoscopy is demonstrated in a bronchial tree phantom. In conclusion, this work contributes to the development of a toolbox of soft robotic solutions for MIS and endoscopic applications, by validating and characterizing a promising design, describing versatile and scalable fabrication methods, allowing a better understanding of the influence of the material stiffness on the actuator capabilities, and demonstrating the usability of the solution in a potential use-case.